Tyk2 is a tumor suppressor in colorectal cancer. (31st December 2022) - Moritsch, Stefan; Mödl, Bernadette; Scharf, Irene; Janker, Lukas; Zwolanek, Daniela; Timelthaler, Gerald; Casanova, Emilio; Sibilia, Maria; Mohr, Thomas; Kenner, Lukas; Herndler-Brandstetter, Dietmar; Gerner, Christopher; et al.
ABSTRACT: Janus kinase Tyk2 is implicated in cancer immune surveillance, but its role in solid tumors is not well defined. We used Tyk2 knockout mice (Tyk2 Δ/Δ ) and mice with conditional deletion of Tyk2 in hematopoietic (Tyk2 ΔHem ) or intestinal epithelial cells (Tyk2 ΔIEC ) to assess their cell type-specific functions in chemically induced colorectal cancer. All Tyk2-deficient mouse models showed a higher tumor burden after AOM-DSS treatment compared to their corresponding wild-type controls (Tyk2 +/+ and Tyk2 fl/fl ), demonstrating tumor-suppressive functions of Tyk2 in immune cells and epithelial cancer cells. However, specific deletion of Tyk2 in hematopoietic cells or in intestinal epithelial cells was insufficient to accelerate tumor progression, while deletion in both compartments promoted carcinoma formation. RNA-seq and proteomics revealed that tumors of Tyk2 Δ/Δ and Tyk2 ΔIEC mice were immunoedited in different ways with downregulated and upregulated IFNγ signatures, respectively. Accordingly, the IFNγ-regulated immune checkpoint Ido1 was downregulated in Tyk2 Δ/Δ and upregulated in Tyk2 ΔIEC tumors, although both showed reduced CD8 + T cell infiltration. These data suggest that Tyk2 Δ/Δ tumors are Ido1-independent and poorly immunoedited while Tyk2 ΔIEC tumors require Ido1 for immune evasion. Our study shows that Tyk2 prevents Ido1 expression in CRC cells and promotes CRC immune surveillance in the tumor stroma. Both of these Tyk2-dependent mechanisms must work together to prevent CRC progression.